Migration, Schizophrenia, and Crime: A Study From a Forensic Psychiatric Sample - He, Yong; Gu, Yan; Wang, Shujian; Li, Yan; Li, Gangqin; Hu, Zeqing (Frontiers in Psychiatry, 2022)
Background The association between mental health problems and crime in immigrants has attracted recent academic interest, with results suggesting that there were possible interactions between immigration, schizophrenia, and criminal behavior. However, very few studies have examined these interactions, especially in developing countries that have mass internal immigration. Therefore, this study sought to identify the associations between the sociodemographic, clinical, and criminal factors in migrants and non-migrants with schizophrenia who had been involved in criminal activities in China. Methods Forensic archives of suspects who had been referred for criminal responsibility assessments in the Sichuan West China Forensic Center from January 2015 to December 2019 were reviewed. The sociodemographic, and criminal activity information of the suspects were extracted, while the clinical and social function were measured by the Brief Psychiatric Rating Scale (BPRS) and Social Disability Screening Schedule (SDSS) based on the archives. A Chi-squared test, a T-test, a Mann-Whitney U test, and Multinomial logistic regression were employed for the statistical analysis. Results A total of 552 patients were reviewed and evaluated, 17.2% (n = 95) of which were migrants. The migrant patient group was younger than the non-migrant patient group. The BPRS and SDSS scores for the migrant patient group were lower than for the non-migrant patient group. The migrant patient group had more work experience and more had been employed at the time of the crime than the non-migrant patient group. The unemployed migrant patients were more likely to commit a property-related crime. Conclusions Compared to the non-migrant schizophrenia patient group, the migrant patient group had less severe psychiatric symptoms and less social function impairments. Employment was an important factor in preventing criminality in patients with schizophrenia, especially for migrant patients. Vocational rehabilitation focuses on developing appropriate employment that can significantly assist in schizophrenia patient recovery, which in turn could reduce their chances of committing crime. Besides, reducing other obstacles to stigma, housing and health insurance would also be beneficial to crime reduction.